Particle Flow Simulation of the Mechanical Properties and Fracture Behavior of Multi-Mineral Rock Models with Different Fractal Dimensions - Run Shi; Huaiguang Xiao (Fractal and Fractional)
To study the effects of rock models with different fractal dimensions on their mechanical properties and fracture behavior, three representative numerical rock models, including the digital texture model, the Voronoi polygon model, and the Weibull distribution model, are established in this paper. These models are used to simulate the structure of multi-mineral rocks and to investigate the influence of fractal dimensions on the mechanical properties and fracture behavior of rocks. Uniaxial compression numerical tests are carried out on 2D and 3D intact rocks under different fractal dimensions using the particle flow simulation method. The relationship between fractal dimensions and uniaxial compression strength and fracture behavior was analyzed. The results show that the fractal dimension of the Weibull distribution model is the largest, followed by the digital texture model, and the fractal dimension of the Voronoi polygon model is the smallest. With the increase in fractal dimension, the uniaxial compressive strength of intact rocks increases significantly, and their relationship is approximately linear. The influence of fractal dimension on rock strength shows a similar trend in both the 2D and 3D models. This study provides a new perspective for the application of fractal dimensions in multi-mineral rock models.